ISLAMIC LAW IN THE LAND OF MALAY - Adrianus Chatib; Munsarida - (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to find out in-depth: 1) how the implementation of law enforcement in the Siak Sri Indrapur, Riau and how it is enforced in the Jambi Malay, both related to criminal, civil and moral matters; 2) What is the contribution of Bab al-Qawa'id and Law 20 to law enforcement and what values ​​can be embraced by society to organize law enforcement in Indonesia today; 3) why the two governments adhere to the same or similar legal principles. The researcher used qualitative with descriptive method. The data collection technique is a literature review with documentation technique, while the data analysis technique is content analysis. The findings of the study are: 1) The law enforcement in the Siak Sri Indrapura through what is stated in Chapter Al-Qawa'id manuscript, both relating to criminal, civil, moral/religious and custom textually the text and its implementation that the law in that area is well established. Law enforcement in Jambi Sultanate refers to the law of 'nun Duapuluh.' It is running well as well as law enforcement in Siak sultanate. It is just that, judging from the sources of law used, whether criminal, civil, moral or religious, or customary, the law is not as elaborated as Chapter al-Qawa'id. It is not too difficult to understand because the Law of 'Nun Duapuluh' is older than Chapter al-Qawa'id by about one century. The law in Chapter al-Qawa'id and the law of 'nun Duapuluh' have contributed to law enforcement in their time, and both have contributed to the cultivation of values ​​that can be guided for law enforcement today in 'Tanah Air.' Abstrak: Penelitian ini bertujuan untuk mengetahui secara mendalam: 1) bagaimana implementasi penegakan hukum di kesultanan Siak Sri Indrapur, Riau dan bagaimana pula penegakannya di kesultanan Melayu Jambi, baik yang berkaitan dengan pidana, perdata maupun moral; 2) Sejauhmana kontribusi Bab al-Qawa’id dan Undang- undang nan 20 terhadap penegakan hukum dan nilai-nilai apa yang dapat dianut masyarakat untuk menata penegakan hukum di Indonesia dewasa ini; 3) kenapa kedua pemerintahan itu menganut asas hukum yang sama atau berkemiripan. Peneliti menggunakan kualitatif dengan metode deskriptif. Teknik dalam pengumpulan data adalah kajian pustaka dengan teknik dokumentasi, sedangkan teknik analisis datanya adalah teknik content analysis. Temuan dari penelitian ini adalah: 1) bahwa penegakan hukum di kesultanan Siak Sri Indrapura melalui apa yang dituangkan dalam naskah Bab al-Qawa’id, baik yang berkaitan dengan pidana, perdata, moral/agama dan adat secara tekstual naskah dan implementasinya bahwa hukum di wilayah itu sudah ditegakkan dengan baik. Penegakan hukum di kesultanan Jambi merujuk pada Undang-undang 'nan Duapuluh' berjalan dengan baik seperti halnya penegakan hukum di kesultanan Siak. Hanya saja, dilihat dari sumber hukum yang dipakai baik pidana, perdata, moral atau agama maupun adat, undang-undang 'nan Duapuluh' tidak seterurai Bab al-Qawa'id. Hal itu, tidaklah terlalu sulit memahaminya, karena Undang-undang 'nan Duapuluh' lebih tua dari Bab al-Qawa'id sekitar 1 abad. Kitab perundang-undangan bab al-Qawa'id dan kitab undang-undang 'nan Duapuluh' telah memberikan kontribusi pada penegakan hukum pada masanya dan keduanya telah pula memberikan andil terhadap penanaman nilai-nlai yang dapat dipedomani untuk penegakan hukum dewasa ini di Tanah Air. Kata Kunci: Hukum Islam, Implementasi, Bab al-Qawa’id, Undang-undang 'Nan Duapuluh'